1986
DOI: 10.1161/01.hyp.8.6.526
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular calcium and altered vascular responsiveness in the deoxycorticosterone acetate-salt rat.

Abstract: SUMMARY This study investigated the effects of altered extracellular Ca 2+ on in vitro femoral arterial smooth muscle responsiveness in deoxycorticosterone acetate (DOCA)-salt hypertensive rats. Compared with controls, femoral arteries from DOCA-salt rats snowed a significant increase in sensitivity to KCI and norepinephrine in normal Ca 2+ (2.5 mM). Although no difference in maximal contractile response to KCI was observed between groups, there was a significant difference in maximal response to norepinephrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
1

Year Published

1988
1988
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 17 publications
3
13
0
1
Order By: Relevance
“…Hypertensive rats showed not only more hypertrophy of vascular tissue and the adrenal gland, but also increasing thickness of media, compared to the normotensive rats. A number of studies have corroborated the results of our present study 6,7) . Growth of vascular wall thickness was verified as a coincident tendency in the primary hypertension animal model, and this result is considered to be highly significant 21) .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Hypertensive rats showed not only more hypertrophy of vascular tissue and the adrenal gland, but also increasing thickness of media, compared to the normotensive rats. A number of studies have corroborated the results of our present study 6,7) . Growth of vascular wall thickness was verified as a coincident tendency in the primary hypertension animal model, and this result is considered to be highly significant 21) .…”
Section: Discussionsupporting
confidence: 91%
“…This is especially true in the case of forceful hyperplasia or the action of catecholamine which is known to have an adverse effect on the mechanism pain induction, especially in hypertension, because it is likely to aggravate the excessive tension in the vascular smooth muscle cells that occurs in this disease 3,19) . Studies by Dahl and others have reported that the saltdependent hypertension and the DOCA-salt hypertension animal models are important models for experiments in hypertension research 4,6,20) . There is a direct correlation between the secondary hypertension of Korean adults and the DOCA-salt hypertension animal model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soltis and Field (27) observed that femoral arteries from DOCA rats exhibit an increased reactivity to KCl and to norepinephrine only in the presence of normal extracellular Ca 2+ concentration, but not in the presence of low extracellular Ca 2+ . These authors suggested that the increased reactivity to KCl in arteries from hypertensive rats is related to an increased sensitivity to extracellular Ca 2+ .…”
Section: Abnormalities Of Vascular Function Vs Ca 2+ Handlingmentioning
confidence: 99%
“…Furthermore, Soltis and Field (37) reported an increased reactivity to KCl and to norepinephrine in femoral arteries from DOCA rats, which was related to increased sensitivity to extracellular Ca 2+ , supporting the suggestion of an augmented membrane permeability to Ca 2+ . While an increased membrane permeability to Ca 2+ in DOCA aortic cells can account for the alterations observed, alternative mechanisms must be considered.…”
Section: µM Serotoninmentioning
confidence: 60%